Site selectivities in fluorination. Issue 9 (28th February 2018) - Ishida, Syo; Sheppard, Tom; Nishikata, Takashi
Graphical abstract: Highlights: Recent digests on site-selective fluorinations. Fluorination of alcohols, alkyl halides and CH bonds. Overview of each selective fluorination reactions including catalytic reaction. Abstract: In the synthesis of bio-active compounds, fluorinated compounds play a prominent role. However, the site-selective fluorination of organic molecules is often challenging, because activation of a reaction site using a fluorinating reagent can be difficult in a substrate possessing many functional groups. This digest introduces recent examples of site-selective fluorination reactions.